101k views
2 votes
Solve for.x 3x-2(6-x)=7x+2(5+x)-6

Solve for.x 3x-2(6-x)=7x+2(5+x)-6-example-1

2 Answers

4 votes

Answer:

A) x = -4

Explanation:


3x-2\left(6-x\right)=7x+2\left(5+x\right)-6\\\\\mathrm{Expand\:}3x-2\left(6-x\right):\quad 5x-12\\\\\mathrm{Expand\:}7x+2\left(5+x\right)-6:\quad 9x+4\\5x-12=9x+4\\\\\mathrm{Add\:}12\mathrm{\:to\:both\:sides}\\5x-12+12=9x+4+12\\\\Simplify\\5x=9x+16\\\\\mathrm{Subtract\:}9x\mathrm{\:from\:both\:sides}\\5x-9x=9x+16-9x\\\\Simplify\\-4x=16\\\\\mathrm{Divide\:both\:sides\:by\:}-4\\(-4x)/(-4)=(16)/(-4)\\\\Simplify\\x=-4

User Brad Decker
by
4.6k points
6 votes
x=4 , soo yea hope this helps , lol
User Catchwa
by
4.8k points